1982
DOI: 10.1007/bf00028325
|View full text |Cite
|
Sign up to set email alerts
|

Alternative methods of interpreting measurements of resistance to the leafhopper Empoasca kraemeri Ross and Moore in the common bean, Phaseolus vulgaris L.

Abstract: Phaseolus vulgaris, common bean, Empoasca kraemeri, leafhopper, components of resistance, resistance to insects . SUMMARY Appropriate definitions of, and methods of measuring, resistance are sought using Phaseolus vulgaris, a major source of protein in Latin America, and its most important pest, Empoasca kraemeri . The concepts of general vigour and narrow-sense resistance are defined : these two components make up broad-sense resistance . The validity of these definitions, which depend on the inclusion of tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
0
6
0
Order By: Relevance
“…Data were collected from three experiments described in an earlier paper (GALWEY & EVANS, 1982). Data were collected from three experiments described in an earlier paper (GALWEY & EVANS, 1982).…”
Section: Materialsandfieldmethodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Data were collected from three experiments described in an earlier paper (GALWEY & EVANS, 1982). Data were collected from three experiments described in an earlier paper (GALWEY & EVANS, 1982).…”
Section: Materialsandfieldmethodsmentioning
confidence: 99%
“…In each of these experiments, numerical scores based on visual assessment of E. kraemeri damage symptoms in the unprotected sub-plots, and of general vigour in the protected sub-plots and measurements of seed yield per plant, were taken using methods described in an earlier paper (GALWEY & EVANS, 1982). In each of these experiments, numerical scores based on visual assessment of E. kraemeri damage symptoms in the unprotected sub-plots, and of general vigour in the protected sub-plots and measurements of seed yield per plant, were taken using methods described in an earlier paper (GALWEY & EVANS, 1982).…”
Section: No Protectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resistance to E. kraemeri has been shown to be quantitatively inherited (CIAT 1978) with low heritability (Galwey and Evans 1982). Kornegay and Cardona (1990) reported that selections in the F 4 and F 5 generations generally produced lines with greater unprotected yields than did selections in the F 2 or F 3 generations.…”
mentioning
confidence: 99%